(untitled) (EAAE Annual Conference Proceedings, 2023)
There is a plan to be able to opt for a better future, and this is the wellknown 2030 Agenda. An opportunity for us to promote prosperity while protecting the planet. The seventeen sustainable development goals and the targets linked to them contained in the 2030 agenda seek, among other objectives, the elimination of poverty, the universalization of quality education, achieve equal rights between genders, the defence of the environment, the construction of a decent and safe human habitat or lay the foundations to build equitable and inclusive development. It does not aspire to provide material goods but to ensure human rights.